Administrative Leaders ’Awareness of Emotional Intelligence and its Role in the Effectiveness of Leadership at King Saud University - Alfrayan, Njoud Abdulaziz; Alaisa, Guzayel Saad (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the administrative leaders 'awareness of emotional intelligence and its role in the effectiveness of leadership at King Saud University in Riyadh and to identify the extent of administrative and academic leaders 'familiarity with the concept and elements of emotional intelligence, it also aimed to recognize the role of emotional intelligence in the effective leadership. In this study, the researcher used the descriptive-analytical method, she also used the questionnaire as the study tool, which was distributed to the study community, which consisted of administrative and academic leadership at King Saud University in Riyadh, the number reached (151) questionnaires suitable for analysis, the results showed that the administrative and academic leadership at King Saud University have awareness of the concept and elements of emotional intelligence to an acceptable degree, where social skills and motivation came in a higher degree for leaders, followed by self-awareness after that empathy and in the last emotional management. The results showed the leadership effectiveness has a strongly acceptable degree. The results also showed that there is a strong direct correlation between the awareness of administrative and academic leaders, with the concept and elements of emotional intelligence and leadership effectiveness. The study recommended the need for administrative leadership at King Saud University to pay attention to emotional intelligence in its five elements, to reach a distinguished level of performance and distinguished leadership of the university's administrations, especially after the university's independence. In addition to conducting training courses that help increase the emotional intelligence skills of both managers and employees, especially training them to manage their feelings and recognize the feelings of others, so that emotional intelligence becomes part of the organizational culture of the university.
Keywords: emotional intelligence; administrative leadership; academic leadership; leadership effectiveness